Answer:
Fe(iii)2O3 + 3CO ===> 2Fe + 3CO2
Explanation:
Fe(iii)2O3 + CO ===> Fe + CO2
The best thing to do is start with the Oxygens. They are the most complicated.
Fe(iii)2O3 + 3 CO ===> Fe + 3 CO2
Unfortunately this equation is a bit of by guess and by gosh. You need to balance the oxygens so that the total is an even number. That's because the right hand side is always going to be even. [The 2 on CO2 will make anything in front of it even).
So there are 6 oxygens on the left and 6 on the right. The carbons by accident are balanced with this maneuver. So all that is left is the irons.
Fe(iii)2O3 + 3CO ===> 2Fe + 3CO2
This equation is a bit nasty, but in higher chemistry courses, you will learn how to make it a whole lot simpler. For now you are just going to have to put up with the nastiness of the question and guess.